2015
DOI: 10.17660/actahortic.2015.1075.20
|View full text |Cite
|
Sign up to set email alerts
|

Green Manures in 'Kent' Mango Orchard

Abstract: Continuous and intensive use of the soils of the Lower-Middle São Francisco River Valley (Vale do Submédio São Francisco) through the growing of mango trees in irrigated systems has caused soil degradation and consequently threatened the quality and sustainability of this agribusiness activity in the region. The predominant soil cover in this region has a sandy texture and low organic matter content and water retention capability, which are further compromised by high temperatures and insolation which cause se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As C4 species have higher photosynthesis potential than C3 species, they can produce more biomass than legume species (Pedroso et al, 2014). Planting these Poaceae species as sole green manure crops is not a common practice but they have been lately tested as part of mixtures of several species planted together (Snapp et al, 2005;Miyazawa et al, 2010;Pimentel et al, 2011;Feitosa et al, 2015;Mouco et al, 2015;Pereira Filho et al, 2016). These mixtures have the potential to maximize biomass production but little is known of their capacity to fix N. Perhaps the lack of information comes from the variability of fixation in the Poaceae, apparently high in some places (Montañez et al, 2009;Morais et al, 2012;Taulé et al, 2012;Baptista et al, 2014;Santos et al, 2017) but completely absent in other places (Biggs et al, 2002;Hoefsloot et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As C4 species have higher photosynthesis potential than C3 species, they can produce more biomass than legume species (Pedroso et al, 2014). Planting these Poaceae species as sole green manure crops is not a common practice but they have been lately tested as part of mixtures of several species planted together (Snapp et al, 2005;Miyazawa et al, 2010;Pimentel et al, 2011;Feitosa et al, 2015;Mouco et al, 2015;Pereira Filho et al, 2016). These mixtures have the potential to maximize biomass production but little is known of their capacity to fix N. Perhaps the lack of information comes from the variability of fixation in the Poaceae, apparently high in some places (Montañez et al, 2009;Morais et al, 2012;Taulé et al, 2012;Baptista et al, 2014;Santos et al, 2017) but completely absent in other places (Biggs et al, 2002;Hoefsloot et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Green manure may counterbalance the rapid decrease in soil organic matter brought by the high rates of organic matter decomposition, which occur under conditions of high temperature and ultraviolet radiation (Parton et al, 2007;King et al, 2012) and high soil humidity (Lee et al, 2014). In spite of green manure mixtures being a growing practice in the region (Pimentel et al, 2011;Feitosa et al, 2015;Mouco et al, 2015;Pereira Filho et al, 2016), determinations of their biomass production and especially N fixation are scarce. Periodical incorporation of spontaneous vegetation is also a growing and less studied practice in the region.…”
Section: Introductionmentioning
confidence: 99%
“…To estimative of C input from aboveground and belowground biomass we assumed a C content of 45% dry matter. Further details about the long-term field experiments can be found elsewhere (Antonio et al, 2019;Brandao et al, 2017;Freitas et al, 2019;Giongo et al, 2016;Mouco et al, 2015).…”
Section: Aboveground and Belowground C Inputsmentioning
confidence: 99%
“…Although many studies concluded that these green manures are a viable practice (Hunter et al, 2021;De Notaris et al, 2021;Hu et al, 2023) they are not used in many irrigated areas of the world. In the large irrigated fruit producing areas in the São Francisco river valley, in the Brazilian semi-arid northeast region, the practice of cover crops is almost completely absent (Pimentel et al, 2011;Feitosa et al, 2015;Mouco et al, 2015;Pereira Filho et al, 2016). To promote their use, appropriate species must be sellected and the best management of the produced biomass has to be determined (Ferreira Neto et al, 2017;De Notaris et al, 2021).…”
Section: Introductionmentioning
confidence: 99%